2019
DOI: 10.1111/joa.13011
|View full text |Cite
|
Sign up to set email alerts
|

Callosal septa express guidance cues and are paramedian guideposts for human corpus callosum development

Abstract: The early development and growth of the corpus callosum are supported by several midline transient structures in mammals that include callosal septa (CS), which are present only in the second half of gestation in humans.Here we provide new data that support the guidance role of CS in corpus callosum development, derived from the analysis of 46 postmortem fetal brains, ranging in age from 16 to 40 post conception weeks (PCW). Using immunohistochemical methods, we show the expression pattern of guidance cues eph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 95 publications
(119 reference statements)
0
13
0
1
Order By: Relevance
“…Developing callosal fibers grow through complex pathways and cross the midline using different substrates in transient fetal structures such as the callosal septa. The callosal septa are prominent between 18 and 34 wk, and their biochemical composition is dynamically over this period, including changes in the expression of axonal guidance molecules, cellular matrix, and ECM constituents, which are likely to affect tensor metrics (64,65). Previous studies have also identified differences in the growth rate of different sections of the CC, with the genu growing at a faster rate than the body and the splenium during fetal development, but then after birth, mature myelination is observed in the splenium before the genu (55,51,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Developing callosal fibers grow through complex pathways and cross the midline using different substrates in transient fetal structures such as the callosal septa. The callosal septa are prominent between 18 and 34 wk, and their biochemical composition is dynamically over this period, including changes in the expression of axonal guidance molecules, cellular matrix, and ECM constituents, which are likely to affect tensor metrics (64,65). Previous studies have also identified differences in the growth rate of different sections of the CC, with the genu growing at a faster rate than the body and the splenium during fetal development, but then after birth, mature myelination is observed in the splenium before the genu (55,51,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Sections were then incubated with primary antibodies for 48 h at 4 ˚C (AXIN2 1:100, FZD1 1:100, LEF1 1:100, AQP1 1:100, OTX2 1:50, β-Catenin cell signaling 1:400, β-Catenin Dako 1:200), washed and subsequently incubated with secondary antimouse or antirabbit antibodies diluted in PBS (at 1:1000) for 2 h at the room temperature. For visualization of the specific immune reactivity following secondary antibodies were used according to the laboratory protocol 63 : the donkey antimouse IgG Alexa fluor-plus 488, donkey antirabbit IgG Alexa fluor-plus 647, donkey antirabbit IgG 488, donkey antimouse IgG Alexa fluor 546 were used. Sections were covered with a mounting medium containing DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…The brain structure was analyzed on coronal sections, cryo-sections 60 µm thick for P1, and paraffin 14 µm thick for P105, stained by cresyl-violet (modification by Nissl: 0.5% Cresyl violet, Chemika, Girraween, NSW, Australia). The differential expression of specific proteins was examined by immunofluorescent (IF; free-floating 60 μm thick cryo-sections for P1; glass-mounted 14 µm thick sections for P105) and classic non-fluorescent (IHC) (free-floating 60 μm thick cryo-sections for P1; glass-mounted 14 µm thick sections for P105) staining as described in our previous publications ( Bobić Rasonja et al, 2019 ; Culjat and Milošević, 2019 ), and given in more details in the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%